PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMP PADA MATERI ZAT ADITIF - Latifatul Ilmi; Beni Setiawan (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
This study aimed to describe the improvement of students’learning outcomes on additive substances using the STAD cooperative learning model. This study used a pre-experimental with one group pretest posttest design. Samples in this study were 37 students. The data were collected using observation, questionnaires, and tests. The implementation of learning obtained high results with very good categories in the first and second meetings. The improvement in students' learning outcomes was analyzed using paired t-test and N-Gain test. Paired t-test result indicated that there was an effect of treatment on student learning outcomes. As for the N-Gain test result obtained a value of 0,75 that indicated an increase in the high category. The results of the student responses got a high percentage which meant that students responded very well to STAD cooperative learning model. Based on theseresults, it can be concluded that STAD cooperative learning model could improve students' learning outcomes.